Insulation heat dissipation coating composition for lithium battery and preparation method of insulation heat dissipation coating composition

By combining modified epoxy resin and thermally conductive filler, an insulated heat dissipation coating of lithium batteries with excellent weather resistance and heat dissipation performance was prepared, which solved the problem of poor performance of lithium batteries in high temperature environments and achieved efficient heat dissipation of lithium batteries and insulation performance extend the service life of the product.

CN119286364AInactive Publication Date: 2025-01-10CTRON ADVANCED MATERIAL CO LTD

Patent Information

Application Number
CN202411809363.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery heat dissipation coatings have poor performance in high temperature environments and are difficult to take into account both thermal conductivity and insulation performance, which affects the service life of the battery.

Method used

Modified epoxy resin and thermal filler (fluorinated graphene, insulated carbon black, boron nitride) are combined to prepare excellent weather resistance, moisture and heat resistance, wear resistance and chemical corrosion resistance through specific processes. Insulating heat dissipation coating composition improves the adhesion and heat dissipation properties of the coating.

Benefits of technology

It realizes efficient heat dissipation and insulation performance of lithium battery coating, extends the service life of the product, and adapts to harsh environmental conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of insulation and heat dissipation coatings, and particularly relates to an insulation and heat dissipation coating composition for a lithium battery and a preparation method of the insulation and heat dissipation coating composition. The insulating heat dissipation coating composition is prepared from the following raw materials: modified epoxy resin, heat conduction filler, a defoaming agent, a flatting agent, a curing agent and a solvent, a preparation method of the modified epoxy resin comprises the following steps: firstly, preparing fluorinated silane by utilizing an epoxy compound to perform ring-opening reaction and esterification reaction, and then preparing the modified epoxy resin by taking the fluorinated silane, bismaleimide and bisphenol A epoxy resin as raw materials through chain extension reaction. According to the invention, the modified epoxy resin, the heat-conducting filler and other raw materials are compounded, and the prepared coating composition has excellent weather resistance, heat and humidity resistance, wear resistance and chemical corrosion resistance by adjusting the raw material ratio and optimizing the process conditions, and also keeps good adhesive force, impact resistance, heat dissipation and insulativity at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of insulating heat dissipation coatings, and in particular relates to an insulating heat dissipation coating composition for lithium batteries and a preparation method thereof. Background Art

[0002] Lithium batteries generate heat during the charging and discharging process, especially when charging and discharging at high currents. Due to the structural characteristics of lithium batteries, there are significant differences in thermal conductivity in different directions, so different heat dissipation methods have significant differences in efficiency. Inappropriate heat dissipation methods may also cause severe temperature gradients within the battery, affecting the internal current distribution of the battery, resulting in inconsistent internal battery degradation, and seriously shortening the service life of the lithium battery. Insulating heat dissipation coatings are a type of coating used in electronic devices to improve heat dissipation efficiency while maintaining electrical insulation properties. With the rapid development of electronic technology, especially in the fields of high integration technology, microelectronics packaging technology, high-power LED technology, and supercomputers, the requirements for heat dissipation in electronic equipment are becoming increasingly stringent. Insulating heat dissipation coatings can form a protective layer on electronic devices and equipment that is highly thermally conductive, corrosion-resistant, and has good bonding strength, thereby achieving more effective heat dissipation.

[0003] The patent application number CN201910133612.0 provides a composite graphene three-proof heat dissipation coating for the electronics industry, including the following raw materials: epoxy resin, deionized water, graphite oxide, graphene, graphene dispersion, leveling agent, wetting dispersant, ethanol solvent, perfluoroacrylate, acrylic resin, polyurethane, silicone, thickener. Compared with the existing technology, the coating provided by the invention has the functions of non-toxicity, high hiding power, high adhesion, mildew resistance, moisture resistance, and salt spray resistance, while effectively conducting heat and dissipating heat of electronic products. Epoxy resin has excellent bonding properties, mechanical properties, chemical stability, and easy processing and molding, but its cured product has the advantages of high adhesion, high mechanical properties, chemical stability, and easy processing and molding, but its cured product has the advantages of high adhesion, high hiding power, high adhesion, mildew resistance, moisture resistance, and salt spray resistance, while effectively conducting heat and dissipating heat of electronic products. Epoxy resin has excellent bonding properties, mechanical properties, chemical stability, and easy processing and molding, but its cured product has the advantages of high adhesion, high mechanical properties, chemical stability, easy processing and molding, etc. It is brittle, easy to crack, and has poor resistance to moisture and heat, which leads to poor performance of the coating product. The patent with application number CN201711343012.4 provides a graphene heat dissipation coating, including the following raw materials: graphene slurry, adhesive, and diluent, wherein the graphene slurry includes graphene powder, surface treatment agent, and solvent. The graphene heat dissipation coating provided by this invention plays a role in improving the thermal radiation coefficient of the coating in the entire double-layer coating system, while also improving the adhesion of the upper coating. While ensuring the thermal radiation coefficient of the coating, the bottom and upper layers increase the microscopic surface area of ​​the coating after curing through the rough structure of the upper coating, further improving the heat dissipation capacity of the coating. With the miniaturization and increased integration of electronic components, the power density per unit area or volume continues to increase, resulting in a sharp increase in heat generation. In order to ensure that electronic components can work normally and reliably in a high-temperature environment, heat must be dissipated in a timely manner to prevent performance degradation, shortened life, and even damage due to overheating. In some special occasions, such as electronic information, integrated circuits, and aerospace electronic equipment, in addition to requiring the material to have thermal conductivity, it is also required to have excellent insulation properties.

[0004] How to use composite material technology to combine thermal conductive materials and insulating materials through specific process methods to form new materials with both thermal conductive and insulating properties has become one of the important challenges facing the current field of materials science. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide an insulating heat-dissipating coating composition for lithium batteries and a preparation method thereof. By utilizing composite material technology, thermally conductive materials and insulating materials are combined through specific process methods. The prepared coating composition has excellent comprehensive performance and meets the market demand for thermally conductive insulating composite materials.

[0006] The technical solutions adopted by the present invention to achieve the above-mentioned purpose are: An insulating heat dissipation coating composition for lithium batteries, comprising the following raw materials in parts by weight: 50-70 parts of a modified epoxy resin, 10-20 parts of a thermally conductive filler, 0.1-0.5 parts of a defoaming agent, 0.1-5 parts of a leveling agent, 5-10 parts of a curing agent, and 20-40 parts of a solvent; The preparation method of the modified epoxy resin is as follows: S1. Mix 3-glycidyloxypropyltriethoxysilane and toluene at room temperature, then raise the temperature to 85-95°C and stir for 5-15 minutes. Then, add 3-aminobutyric acid and chromium acetate in sequence, continue stirring and react for 5-7 hours, cool to room temperature, and purify to obtain aminosilane; S2. Evenly mix the aminosilane obtained in step S1, 2-cyano-3-(4-fluorophenyl)propionic acid, cyclohexane, and p-toluenesulfonic acid at room temperature, then stir and heat to 70-80° C., react under reflux for 4-8 hours, cool to room temperature, and purify to obtain fluorinated silane; S3, mixing bismaleimide and the fluorinated silane obtained in step S2 uniformly at room temperature, then stirring and heating to 160-170° C., reacting for 20-40 minutes, then lowering the temperature to 75-90° C., adding bisphenol A epoxy resin, continuing to stir and react for 1-3 hours, and cooling to room temperature to obtain a modified epoxy resin; Among them, the synthetic route of fluorinated silane is as follows: ; .

[0007] The present invention uses 3-glycidyloxypropyltriethoxysilane and 3-aminobutyric acid as starting materials, and an epoxy compound ring-opening reaction occurs under the catalysis of chromium acetate to obtain aminosilane; then, aminosilane and 2-cyano-3-(4-fluorophenyl)propionic acid are used as raw materials, and an esterification reaction occurs under the catalysis of p-toluenesulfonic acid to obtain fluorinated silane; finally, fluorinated silane, bismaleimide, and bisphenol A epoxy resin are used as raw materials to prepare a modified epoxy resin through a chain extension reaction. Modifying epoxy resin with maleimide and silicone is an effective method to improve material properties. Studies on the curing behavior and performance of bismaleimide-modified epoxy resins show that the addition of bismaleimide can improve the thermal stability of the epoxy resin system; silicone-modified epoxy resins can improve the toughness, impact resistance, and heat resistance of the resin, resulting in better economic benefits.

[0008] Furthermore, the mass volume ratio of 3-glycidyloxypropyltriethoxysilane to toluene in step S1 is 0.2-0.3 g / mL, and the molar ratio of 3-glycidyloxypropyltriethoxysilane, 3-aminobutyric acid, and chromium acetate is 1.2:0.8-1.0:0.014-0.017; the mass volume ratio of aminosilane to cyclohexane in step S2 is 0.15-0.25 g / mL, and the molar ratio of aminosilane, 2-cyano-3-(4-fluorophenyl)propionic acid, and p-toluenesulfonic acid is 1.0:0.9-1.1:0.01-0.03; the mass ratio of bismaleimide, fluorinated silane, and bisphenol A epoxy resin in step S3 is 5:2.3-2.6:4.5-5.5.

[0009] Furthermore, the preparation method of the thermal conductive filler is: dispersing a silane coupling agent in an ethanol aqueous solution, then adding fluorinated graphene, insulating carbon black, and boron nitride, ultrasonically dispersing for 20-40 minutes, then stirring and reacting at 50-70°C for 1-3 hours, cooling to room temperature, grinding, and drying to obtain the thermal conductive filler; wherein, the mass ratio of the fluorinated graphene, insulating carbon black, and boron nitride is 10-30:30-60:0.5-5, the mass ratio of the silane coupling agent to the fluorinated graphene is 8-10:1, the silane coupling agent is silane coupling agent KH550, the mass fraction of ethanol in the ethanol aqueous solution is 75-85%, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:4-6, the ultrasonic frequency is 20-30KHz, the stirring speed is 1000-1200r / min, and the grinding is performed using a grinder to a particle size of ≤65μm.

[0010] Fluorinated graphene is an important new graphene derivative, a type of two-dimensional material formed by covalently bonding graphene's carbon atoms with fluorine atoms. The introduction of fluorine atoms gives it several excellent properties distinct from graphene, such as insulation, corrosion resistance, thermal conductivity, and lubricity. The high thermal conductivity and excellent electrical insulation properties of fluorinated graphene give it broad application prospects in multiple fields. For example, in microelectronic devices, fluorinated graphene can be used as a thermal interface material, filling the air gap at the device / heat sink interface to establish an effective heat conduction channel and optimize the heat dissipation process. Furthermore, fluorinated graphene can be used to prepare high-thermal conductivity and insulation composite films, high-temperature coatings, anti-wear and lubricating coatings, and corrosion-resistant coatings. The surface of fluorinated graphene is rich in fluorine atoms, which can form good interfacial interactions with a variety of matrix materials, thereby improving the mechanical properties and thermal stability of the composite materials. Insulating carbon black is a carbon material with excellent thermal conductivity. When dispersed in an insulating matrix, it forms a network structure, improving the thermal conductivity of the composite. The surface of insulating carbon black can be modified with various functional groups to enhance its compatibility with the matrix. Boron nitride is a wide-bandgap semiconductor material with high thermal conductivity, good electrical insulation, and chemical stability. Boron nitride can form a synergistic effect with graphene fluoride to improve the thermal conductivity and electrical insulation of the composite. The synergistic use of graphene fluoride, insulating carbon black, and boron nitride can enhance the thermal management capabilities of the composite: the high thermal conductivity of graphene fluoride and boron nitride synergistically improves the thermal conductivity of the composite, while the addition of insulating carbon black further optimizes the heat flow path, achieving efficient thermal management. Furthermore, the synergistic effect of graphene fluoride and insulating carbon black enhances the mechanical properties of the composite, while the addition of boron nitride further improves the wear resistance of the material. The synergistic use of these three materials can also further enhance the corrosion resistance of the composite.

[0011] After modification with the silane coupling agent KH550, the inorganic micro-nanoparticles have a large number of amino groups on their surfaces. These amino groups can chemically react with the epoxy groups in the modified epoxy resin to form covalent bonds. This bonding not only enhances the interfacial interaction between the inorganic micro-nanoparticles and the modified epoxy resin, but also increases the degree of entanglement between the modified epoxy resin molecular chains and the micro-nanoparticles, thereby strengthening the intermolecular forces. This enhanced interaction significantly improves the mechanical properties of the modified epoxy resin. Furthermore, silane-modified micro-nanoparticles improve their compatibility with other raw materials and enhance their dispersion in the modified epoxy resin matrix. This improved dispersion facilitates more uniform stress transfer, significantly improving the material's toughness and impact resistance. Furthermore, the modified micro-nanoparticles can act as a thermal barrier, slowing thermal degradation and increasing the thermal stability of the modified epoxy resin, thereby enhancing the heat resistance of the composite coating.

[0012] Furthermore, the defoaming agent is dimethyl silicone oil or polydimethylsiloxane; the curing agent is one or more of ethylenediamine, triethylamine, and diethylenetriamine; the solvent is ethanol or toluene; and the leveling agent is polyether-modified polydimethylsiloxane.

[0013] The present invention also provides a method for preparing an insulating heat dissipation coating composition for a lithium battery, comprising the following steps: adding a modified epoxy resin to a solvent, mixing evenly, then adding a thermally conductive filler, stirring for 10-20 minutes, then adding a defoaming agent and a leveling agent, continuing to stir for 5-15 minutes, and finally adding a curing agent, stirring and mixing evenly, evenly coating the mixture on a mold surface, and curing to form.

[0014] The present invention has the following beneficial effects: The invention utilizes a two-step method to modify 3-glycidyloxypropyltriethoxysilane to obtain fluorinated silane, and then uses fluorinated silane, bismaleimide and bisphenol A epoxy resin as raw materials to prepare a modified epoxy resin through a chain extension reaction. The modified epoxy resin structure contains fluorine element, benzene ring, cyano group and siloxane. The introduction of siloxane can build a "molecular bridge" between the interfaces of inorganic and organic substances, and utilize two different reactive groups to improve the bonding properties of the resin through covalent bonding, thereby promoting the adhesion of the composite coating material to the surface of the substrate; the introduction of cyano groups enables higher interaction forces between molecules, thereby giving the resin good chemical corrosion resistance. During the resin curing process, the cyano groups will also undergo cross-linking reactions to form a cross-linked network structure, thereby improving the resin's heat resistance, weather resistance and mechanical properties; the introduction of fluorine elements significantly improves the resin's heat resistance, wear resistance and weather resistance by enhancing the resin's thermal stability, reducing surface energy, and improving chemical stability; the joint introduction of benzene rings, cyano groups, and fluorine elements can further improve the heat resistance and weather resistance of the resin material.

[0015] The present invention compounds modified epoxy resin with raw materials such as thermal conductive fillers. By adjusting the raw material ratio and optimizing the process conditions, the prepared coating composition has excellent weather resistance, moisture and heat resistance, wear resistance and chemical corrosion resistance, while also maintaining good adhesion, impact resistance, heat dissipation and insulation properties. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the embodiments described are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application. Bisphenol A epoxy resin, model E51, brand Phoenix brand; fluorinated graphene, fluorine content 60%, particle size D50 50-60μm, layer thickness 5-10nm, purchased from Guangdong Yina Technology Co., Ltd.; insulating carbon black, model MA100R, brand Japan Mitsubishi, particle size 24nm; boron nitride, density 2.29g / cm³, active ingredient content 99%, particle size D50 1-5μm; polydimethylsiloxane, item number lnb-1163, active ingredient content 99%, polyether modified polydimethylsiloxane, item number lnb-1126, active ingredient content 99%, all purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. The raw materials used in the following examples are all common commercially available products.

[0017] Example 1 A method for preparing a modified epoxy resin comprises the following steps: S1. Mix 3-glycidyloxypropyltriethoxysilane and toluene at room temperature, then raise the temperature to 90° C. and stir for 10 min. Then add 3-aminobutyric acid and chromium acetate in sequence, continue stirring and react for 6 h, cool naturally to room temperature, filter, take the filtrate, remove toluene by distillation under reduced pressure, add deionized water and ethyl acetate for extraction, separate the liquids, take the organic phase, concentrate, and vacuum dry to constant weight to obtain aminosilane; wherein the mass volume ratio of 3-glycidyloxypropyltriethoxysilane to toluene is 0.25 g / mL, the molar ratio of 3-glycidyloxypropyltriethoxysilane, 3-aminobutyric acid, and chromium acetate is 1.2:0.9:0.015, and the volume ratio of toluene, deionized water, and ethyl acetate is 2:1:2; S2. At room temperature, the aminosilane obtained in step S1, 2-cyano-3-(4-fluorophenyl)propionic acid, cyclohexane, and p-toluenesulfonic acid were uniformly mixed, then stirred and heated to 75° C., reacted under reflux for 6 hours, naturally cooled to room temperature, filtered, and the filtrate was extracted with ethyl acetate, separated, and the ester layer was taken. The ester layer was washed with a saturated sodium chloride solution and dried over anhydrous sodium sulfate, and then concentrated and dried in vacuo to constant weight to obtain a fluorinated silane; wherein the mass volume ratio of the aminosilane to the cyclohexane was 0.20 g / mL, the molar ratio of the aminosilane, 2-cyano-3-(4-fluorophenyl)propionic acid, and p-toluenesulfonic acid was 1.0:1.0:0.02, and the volume ratio of the cyclohexane to the ethyl acetate was 1:1; The NMR results of fluorinated silane are: 1H NMR (300MHz, DMSO-d6) δ 7.16 (d, 4H), 5.41-5.46 (m, 1H), 4.42-4.44 (m, 1H), 4.17-4.20 (m, 1H), 3.83-3.86 (m, 6H), 3.70-3.74 (m, 2H), 3.42-3.46 (m, 2H), 3.32-3 .35 (m, 3H), 3.15 (d, 1H), 2.58-2.61 (m, 1H), 2.33-2.35 (m, 1H), 1.55 (d, 2H), 1.40-1.44 (m, 2H), 1.21 (t, 9H), 1.10 (d, 3H), 0.56 (t, 2H); S3. Mix bismaleimide and the fluorinated silane obtained in step S2 evenly at room temperature, then stir and heat to 165° C., react for 30 minutes, then lower the temperature to 80° C., add bisphenol A epoxy resin, continue stirring and react for 2 hours, and naturally cool to room temperature to obtain a modified epoxy resin; wherein the mass ratio of bismaleimide, fluorinated silane, and bisphenol A epoxy resin is 5:2.5:5.

[0018] An insulating heat dissipation coating composition for lithium batteries, comprising the following raw materials in parts by weight: 60 parts of modified epoxy resin, 15 parts of thermally conductive filler, 0.3 parts of defoaming agent, 2 parts of leveling agent, 8 parts of curing agent, and 30 parts of solvent; wherein the thermally conductive filler is prepared by: dispersing a silane coupling agent in an ethanol aqueous solution, then adding fluorinated graphene, insulating carbon black, and boron nitride, ultrasonically dispersing for 30 minutes, stirring and reacting at 60°C for 2 hours, naturally cooling to room temperature, grinding, and vacuum drying to constant weight to obtain a fluorinated graphene, insulating carbon black, and boron nitride mass ratio of 0.05. The mass ratio of the silane coupling agent to the fluorinated graphene is 20:45:2.5, the mass ratio of the silane coupling agent to the fluorinated graphene is 9:1, the silane coupling agent is silane coupling agent KH550, the mass fraction of ethanol in the ethanol aqueous solution is 80%, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:5, the ultrasonic frequency is 25 kHz, the stirring speed is 1100 r / min, and the grinding is performed using a grinder to a particle size of ≤65 μm; the defoaming agent is polydimethylsiloxane; the curing agent is diethylenetriamine; the solvent is ethanol; and the leveling agent is polyether-modified polydimethylsiloxane.

[0019] A method for preparing an insulating heat-dissipating coating composition for a lithium battery comprises the following steps: adding a modified epoxy resin to a solvent, mixing the mixture evenly, then adding a thermally conductive filler, stirring at a speed of 1300 r / min for 15 minutes, then adding a defoaming agent and a leveling agent, continuing to stir at a speed of 1300 r / min for 10 minutes, and finally adding a curing agent. After stirring and mixing evenly, the mixture is evenly coated on a mold surface and cured to form the composition; wherein the coating thickness is 100 μm, and the curing and forming is performed using a gradient heating process, specifically comprising the following steps: first, keeping the mixture at 100° C. for 2 hours, then keeping the mixture at 150° C. for 2 hours, and finally keeping the mixture at 180° C. for 2 hours.

[0020] Example 2 A method for preparing a modified epoxy resin comprises the following steps: S1. Mix 3-glycidyloxypropyltriethoxysilane and toluene at room temperature, then raise the temperature to 85° C. and stir for 15 min. Then add 3-aminobutyric acid and chromium acetate in sequence, continue stirring and react for 7 h, cool naturally to room temperature, filter, take the filtrate, remove toluene by distillation under reduced pressure, add deionized water and ethyl acetate for extraction, separate the liquids, take the organic phase, concentrate, and vacuum dry to constant weight to obtain aminosilane; wherein the mass volume ratio of 3-glycidyloxypropyltriethoxysilane to toluene is 0.3 g / mL, the molar ratio of 3-glycidyloxypropyltriethoxysilane, 3-aminobutyric acid, and chromium acetate is 1.2:0.8:0.014, and the volume ratio of toluene, deionized water, and ethyl acetate is 2:1:2; S2. At room temperature, the aminosilane obtained in step S1, 2-cyano-3-(4-fluorophenyl)propionic acid, cyclohexane, and p-toluenesulfonic acid were uniformly mixed, then stirred and heated to 70° C., reacted under reflux for 8 hours, naturally cooled to room temperature, filtered, and the filtrate was extracted with ethyl acetate, separated, and the ester layer was taken. The ester layer was washed with a saturated sodium chloride solution, dried over anhydrous sodium sulfate, and then concentrated and dried in vacuo to constant weight to obtain a fluorinated silane; wherein the mass volume ratio of the aminosilane to the cyclohexane was 0.15 g / mL, the molar ratio of the aminosilane, 2-cyano-3-(4-fluorophenyl)propionic acid, and p-toluenesulfonic acid was 1.0:1.1:0.03, and the volume ratio of the cyclohexane to the ethyl acetate was 1:1; S3. Mix bismaleimide and the fluorinated silane obtained in step S2 evenly at room temperature, then stir and heat to 160° C., react for 40 minutes, then lower the temperature to 75° C., add bisphenol A epoxy resin, continue stirring and react for 3 hours, and naturally cool to room temperature to obtain a modified epoxy resin; wherein the mass ratio of bismaleimide, fluorinated silane, and bisphenol A epoxy resin is 5:2.3:4.5.

[0021] An insulating heat dissipation coating composition for lithium batteries, comprising the following raw materials in parts by weight: 50 parts of modified epoxy resin, 10 parts of thermally conductive filler, 0.1 parts of defoaming agent, 1 part of leveling agent, 5 parts of curing agent, and 20 parts of solvent; wherein the preparation method of the thermally conductive filler is as follows: dispersing a silane coupling agent in an ethanol aqueous solution, then adding fluorinated graphene, insulating carbon black, and boron nitride, ultrasonically dispersing for 40 minutes, stirring and reacting at 70°C for 1 hour, naturally cooling to room temperature, grinding, and vacuum drying to constant weight to obtain fluorinated graphene, insulating carbon black, and boron nitride. The mass ratio is 10:30:0.5, the mass ratio of the silane coupling agent to the fluorinated graphene is 8:1, the silane coupling agent is silane coupling agent KH550, the mass fraction of ethanol in the ethanol aqueous solution is 85%, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:6, the ultrasonic frequency is 25KHz, the stirring speed is 1000r / min, and the grinding is performed using a grinder to a particle size of ≤65μm; the defoaming agent is dimethyl silicone oil; the curing agent is ethylenediamine; the solvent is toluene; and the leveling agent is polyether-modified polydimethylsiloxane.

[0022] A method for preparing an insulating heat-dissipating coating composition for a lithium battery comprises the following steps: adding a modified epoxy resin to a solvent, mixing the mixture evenly, then adding a thermally conductive filler, stirring at a speed of 1300 r / min for 10 minutes, then adding a defoaming agent and a leveling agent, continuing to stir at a speed of 1300 r / min for 15 minutes, and finally adding a curing agent. After stirring and mixing evenly, the mixture is evenly coated on a mold surface and cured to form the composition; wherein the coating thickness is 100 μm, and the curing and forming is performed using a gradient heating process, specifically comprising the following steps: first, keeping the mixture at 100° C. for 2 hours, then keeping the mixture at 150° C. for 2 hours, and finally keeping the mixture at 180° C. for 2 hours.

[0023] Example 3 A method for preparing a modified epoxy resin comprises the following steps: S1. Mix 3-glycidyloxypropyltriethoxysilane and toluene at room temperature, then raise the temperature to 95° C. and stir for 5 min. Then add 3-aminobutyric acid and chromium acetate in sequence, continue stirring and react for 5 h, cool naturally to room temperature, filter, take the filtrate, remove toluene by distillation under reduced pressure, add deionized water and ethyl acetate for extraction, separate the liquids, take the organic phase, concentrate, and vacuum dry to constant weight to obtain aminosilane; wherein the mass volume ratio of 3-glycidyloxypropyltriethoxysilane to toluene is 0.2 g / mL, the molar ratio of 3-glycidyloxypropyltriethoxysilane, 3-aminobutyric acid, and chromium acetate is 1.2:1.0:0.017, and the volume ratio of toluene, deionized water, and ethyl acetate is 2:1:2; S2. At room temperature, the aminosilane obtained in step S1, 2-cyano-3-(4-fluorophenyl)propionic acid, cyclohexane, and p-toluenesulfonic acid were uniformly mixed, then stirred and heated to 80° C., reacted under reflux for 4 hours, naturally cooled to room temperature, filtered, and the filtrate was extracted with ethyl acetate, separated, and the ester layer was taken. The ester layer was washed with a saturated sodium chloride solution, dried over anhydrous sodium sulfate, and then concentrated and dried in vacuo to constant weight to obtain a fluorinated silane; wherein the mass volume ratio of the aminosilane to the cyclohexane was 0.25 g / mL, the molar ratio of the aminosilane, 2-cyano-3-(4-fluorophenyl)propionic acid, and p-toluenesulfonic acid was 1.0:0.9:0.01, and the volume ratio of the cyclohexane to the ethyl acetate was 1:1; S3. Evenly mix bismaleimide and the fluorinated silane obtained in step S2 at room temperature, then stir and heat to 170° C., react for 20 minutes, then lower the temperature to 90° C., add bisphenol A epoxy resin, continue stirring and react for 1 hour, and naturally cool to room temperature to obtain a modified epoxy resin; wherein the mass ratio of bismaleimide, fluorinated silane, and bisphenol A epoxy resin is 5:2.6:5.5.

[0024] An insulating heat dissipation coating composition for lithium batteries, comprising the following raw materials in parts by weight: 70 parts of modified epoxy resin, 20 parts of thermally conductive filler, 0.5 parts of defoaming agent, 4 parts of leveling agent, 10 parts of curing agent, and 40 parts of solvent; wherein the preparation method of the thermally conductive filler is as follows: dispersing a silane coupling agent in an ethanol aqueous solution, then adding fluorinated graphene, insulating carbon black, and boron nitride, ultrasonically dispersing for 20 minutes, stirring and reacting at 50°C for 3 hours, naturally cooling to room temperature, grinding, and vacuum drying to constant weight to obtain fluorinated graphene, insulating carbon black, and boron nitride. The molar ratio is 30:60:5, the mass ratio of the silane coupling agent to the fluorinated graphene is 10:1, the silane coupling agent is silane coupling agent KH550, the mass fraction of ethanol in the ethanol aqueous solution is 75%, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:4, the ultrasonic frequency is 25KHz, the stirring speed is 1200r / min, and the grinding is performed using a grinder to a particle size of ≤65μm; the defoaming agent is polydimethylsiloxane; the curing agent is triethylamine; the solvent is ethanol; and the leveling agent is polyether-modified polydimethylsiloxane.

[0025] A method for preparing an insulating heat-dissipating coating composition for a lithium battery comprises the following steps: adding a modified epoxy resin to a solvent, mixing the mixture evenly, then adding a thermally conductive filler, stirring at a speed of 1300 r / min for 20 minutes, then adding a defoaming agent and a leveling agent, continuing to stir at a speed of 1300 r / min for 5 minutes, and finally adding a curing agent. After stirring and mixing evenly, the mixture is evenly coated on a mold surface and cured to form the composition; wherein the coating thickness is 100 μm, and the curing and forming is performed using a gradient heating process, specifically comprising the following steps: first, keeping the mixture at 100° C. for 2 hours, then keeping the mixture at 150° C. for 2 hours, and finally keeping the mixture at 180° C. for 2 hours.

[0026] Comparative Example 1 An insulating heat dissipation coating composition for a lithium battery comprises the following raw materials in parts by weight: 45 parts of the modified epoxy resin prepared in Example 1, 8 parts of a thermally conductive filler, 0.1 parts of a defoaming agent, 1 part of a leveling agent, 4 parts of a curing agent, and 20 parts of a solvent; wherein the thermally conductive filler is prepared by dispersing a silane coupling agent in an ethanol aqueous solution, then adding fluorinated graphene, insulating carbon black, and boron nitride, ultrasonically dispersing for 30 minutes, stirring and reacting at 60°C for 2 hours, naturally cooling to room temperature, grinding, and vacuum drying to constant weight to obtain fluorinated graphene, insulating carbon black, and boron nitride. The mass ratio of the silane coupling agent to the fluorinated graphene is 20:45:2.5, the mass ratio of the silane coupling agent to the fluorinated graphene is 9:1, the silane coupling agent is silane coupling agent KH550, the mass fraction of ethanol in the ethanol aqueous solution is 80%, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:5, the ultrasonic frequency is 25KHz, the stirring speed is 1100r / min, and the grinding is performed by a grinder to a particle size of ≤65μm; the defoaming agent is polydimethylsiloxane; the curing agent is diethylenetriamine; the solvent is ethanol; and the leveling agent is polyether-modified polydimethylsiloxane.

[0027] A method for preparing an insulating and heat-dissipating coating composition for a lithium battery is prepared according to the method described in Example 1.

[0028] Comparative Example 2 A method for preparing a modified epoxy resin comprises the following steps: S1. Mix 3-glycidyloxypropyltriethoxysilane and toluene at room temperature, then raise the temperature to 90° C. and stir for 10 min. Then add 3-aminobutyric acid and chromium acetate in sequence, continue stirring and react for 6 h, cool naturally to room temperature, filter, take the filtrate, remove toluene by distillation under reduced pressure, add deionized water and ethyl acetate for extraction, separate the liquids, take the organic phase, concentrate, and vacuum dry to constant weight to obtain aminosilane; wherein the mass volume ratio of 3-glycidyloxypropyltriethoxysilane to toluene is 0.25 g / mL, the molar ratio of 3-glycidyloxypropyltriethoxysilane, 3-aminobutyric acid, and chromium acetate is 1.2:0.9:0.015, and the volume ratio of toluene, deionized water, and ethyl acetate is 2:1:2; S2. Mix bismaleimide and the aminosilane obtained in step S1 evenly at room temperature, then stir and heat to 160°C, react for 30 minutes, then lower the temperature to 80°C, add bisphenol A epoxy resin, continue stirring and react for 2 hours, and naturally cool to room temperature to obtain a modified epoxy resin; wherein the mass ratio of bismaleimide, aminosilane, and bisphenol A epoxy resin is 5:2.2:5.

[0029] An insulating and heat-dissipating coating composition for a lithium battery and a preparation method thereof are prepared according to the method described in Example 1.

[0030] Comparative Example 3 A method for preparing a modified epoxy resin comprises: uniformly mixing bismaleimide and 3-glycidyloxypropyltriethoxysilane at room temperature, then stirring and heating to 150° C., reacting for 30 minutes, then lowering the temperature to 80° C., adding bisphenol A epoxy resin, continuing to stir and react for 2 hours, and naturally cooling to room temperature to obtain the modified epoxy resin; wherein the mass ratio of bismaleimide, 3-glycidyloxypropyltriethoxysilane, and bisphenol A epoxy resin is 5:2.0:5.

[0031] An insulating heat dissipation coating composition for lithium batteries, comprising the following raw materials in parts by weight: 60 parts of modified epoxy resin, 15 parts of thermally conductive filler, 0.5 parts of defoaming agent, 3 parts of leveling agent, 15 parts of curing agent, and 30 parts of solvent; wherein the preparation method of the thermally conductive filler is as follows: dispersing a silane coupling agent in an ethanol aqueous solution, then adding fluorinated graphene, insulating carbon black, and boron nitride, ultrasonically dispersing for 30 minutes, stirring and reacting at 60°C for 2 hours, naturally cooling to room temperature, grinding, and vacuum drying to constant weight to obtain the fluorinated graphene, insulating carbon black, and boron nitride. The ratio is 20:45:2.5, the mass ratio of the silane coupling agent to the fluorinated graphene is 9:1, the silane coupling agent is silane coupling agent KH550, the mass fraction of ethanol in the ethanol aqueous solution is 80%, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:5, the ultrasonic frequency is 25KHz, the stirring speed is 1100r / min, and the grinding is performed using a grinder to a particle size of ≤65μm; the defoaming agent is polydimethylsiloxane; the curing agent is diethylenetriamine; the solvent is ethanol; and the leveling agent is polyether-modified polydimethylsiloxane.

[0032] A method for preparing an insulating heat-dissipating coating composition for a lithium battery comprises the following steps: adding a modified epoxy resin to a solvent, mixing the mixture evenly, adding a thermally conductive filler, stirring at a speed of 1300 r / min for 15 minutes, adding a defoaming agent and a leveling agent, continuing to stir at a speed of 1300 r / min for 10 minutes, and finally adding a curing agent. After stirring and mixing evenly, the curing agent is evenly coated on a mold surface and cured to form the composition; wherein the coating thickness is 100 μm, and the curing is performed using a gradient heating process, specifically: first, keeping the mixture at 100° C. for 2 hours, then keeping the mixture at 180° C. for 3 hours, and finally keeping the mixture at 200° C. for 2 hours.

[0033] The insulating heat dissipation coating compositions for lithium batteries prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to relevant performance tests. The adhesion performance test was carried out in accordance with GB / T 9286-2021 "Paints and varnishes - Cross-cut test"; the weather resistance test was carried out in accordance with GB / T 1865-2009 "Paints and varnishes - Artificial weathering and artificial radiation exposure to filtered xenon arc radiation", with a test time of 2000h; the moisture and heat resistance test was carried out in accordance with GB / T 1740-2007 "Determination of moisture and heat resistance of paint films", with a test time of 1000h; the impact resistance test was carried out in accordance with GB / T 1732-2020 "Determination of impact resistance of paint films"; the chemical corrosion resistance test was carried out in accordance with GB / T The test was conducted in accordance with the provisions of GB / T 1763-1979, "Determination of Resistance of Paint Films to Chemical Reagents," with the samples placed in 5% H2SO4 and 5% NaOH for 192 hours, respectively. A wear resistance test was conducted using a 5mm diameter GCr15 steel ball in a reciprocating motion with a stroke of 5mm, a load of 3N, a motor speed of 500r / min, and a test time of 20 minutes. The sample loss rate was calculated. The insulation performance test was conducted in accordance with GB / T 1410-2006, "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials," to measure the volume resistivity of the sample. The thermal conductivity test was conducted using a transient plane heat source method thermal conductivity meter. All of the above tests were repeated three times and the average value was obtained. The test results are shown in Table 1. As can be seen from the performance data in Table 1, compared with Comparative Examples 1-3, the insulating and heat-dissipating coating compositions prepared in Examples 1-3 exhibit excellent weather resistance, moisture and heat resistance, wear resistance, and chemical corrosion resistance, while also maintaining good adhesion, impact resistance, heat dissipation, and insulation properties. The insulating heat dissipation coating composition for lithium batteries provided by the present invention has excellent comprehensive performance, can improve product performance, effectively extend the service life of the product, and enable it to adapt to more diverse and harsh environmental conditions.

[0034] Table 1 Performance test results of insulating heat dissipation coating composition for lithium batteries Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Adhesion (grade) 0 0 0 0 0 0 Weather resistance (grade) 0 0 0 1 2 2 Moisture and heat resistance (grade) 1 1 1 1-2 2-3 3 Impact resistance (cm) 65 55 60 50 55 55 Acid resistance No blistering, no spots No blistering, no spots No blistering, no spots No blistering, no spots spot foaming Alkali resistance No blistering, no spots No blistering, no spots No blistering, no spots No blistering, no spots spot foaming Loss rate (%) 2.31 2.39 2.26 2.74 3.86 4.03 Volume resistivity (Ω·cm) <![CDATA[1.7×10 7 ]]> <![CDATA[1.7×10 7 ]]> <![CDATA[1.8×10 7 ]]> <![CDATA[1.6×10 7 ]]> <![CDATA[1.7×10 7 ]]> <![CDATA[1.6×10 7 ]]> Thermal conductivity (W / (m·K)) 2.65 2.56 2.61 2.37 2.44 2.34 Although the embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. An insulating heat dissipation coating composition for lithium batteries, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of modified epoxy resin, 10-20 parts of thermal conductive filler, 0.1-0.5 parts of defoaming agent, 0.1-5 parts of leveling agent, 5-10 parts of curing agent and 20-40 parts of solvent; The preparation method of the modified epoxy resin is: S1. Mix 3-glycidyloxypropyltriethoxysilane and toluene evenly at room temperature, then raise the temperature to 85-95°C, stir for 5-15 minutes, then add 3-aminobutyric acid and chromium acetate in sequence, continue stirring and react for 5-7 hours, cool to room temperature, and obtain aminosilane after purification; S2, at room temperature, the aminosilane obtained in step S1, 2-cyano-3-(4-fluorophenyl)propionic acid, cyclohexane, and p-toluenesulfonic acid are uniformly mixed, then stirred and heated to 70-80° C., reacted under reflux for 4-8 hours, cooled to room temperature, and purified to obtain fluorinated silane; S3, bismaleimide and the fluorinated silane obtained in step S2 are uniformly mixed at room temperature, then stirred and heated to 160-170°C, reacted for 20-40 minutes, then the temperature was lowered to 75-90°C, bisphenol A epoxy resin was added, the reaction was continued with stirring for 1-3 hours, and cooled to room temperature to obtain a modified epoxy resin.

2. The insulating heat dissipating coating composition for lithium battery according to claim 1, characterized in that: The mass volume ratio of 3-glycidyloxypropyltriethoxysilane to toluene in step S1 is 0.2-0.3 g / mL, and the molar ratio of 3-glycidyloxypropyltriethoxysilane, 3-aminobutyric acid and chromium acetate is 1.2:0.8-1.0:0.014-0.

017.

3. The insulating heat dissipating coating composition for lithium battery according to claim 1, characterized in that: The mass volume ratio of the aminosilane to cyclohexane in step S2 is 0.15-0.25 g / mL, and the molar ratio of the aminosilane, 2-cyano-3-(4-fluorophenyl)propionic acid, and p-toluenesulfonic acid is 1.0:0.9-1.1:0.01-0.

03.

4. The insulating heat dissipating coating composition for lithium battery according to claim 1, characterized in that: The mass ratio of bismaleimide, fluorinated silane and bisphenol A epoxy resin in step S3 is 5:2.3-2.6:4.5-5.

5.

5. The insulating heat dissipating coating composition for lithium battery according to claim 1, characterized in that: The preparation method of the thermal conductive filler is as follows: dispersing a silane coupling agent in an ethanol aqueous solution, then adding fluorinated graphene, insulating carbon black and boron nitride, ultrasonically dispersing for 20-40 minutes, stirring and reacting at 50-70° C. for 1-3 hours, cooling to room temperature, grinding and drying to obtain the thermal conductive filler.

6. The insulating heat dissipating coating composition for lithium battery according to claim 5, characterized in that: The mass ratio of the fluorinated graphene, insulating carbon black and boron nitride is 10-30:30-60:0.5-5, the mass ratio of the silane coupling agent to the fluorinated graphene is 8-10:1, the silane coupling agent is silane coupling agent KH550, the mass fraction of ethanol in the ethanol aqueous solution is 75-85%, and the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:4-6.

7. The insulating heat dissipating coating composition for lithium battery according to claim 5, characterized in that: The ultrasonic frequency is 20-30 KHz, the stirring speed is 1000-1200 r / min, and the grinding is performed by a grinder to a particle size of ≤65 μm.

8. The insulating heat dissipating coating composition for lithium battery according to claim 1, characterized in that: The defoaming agent is dimethyl silicone oil or polydimethylsiloxane; the curing agent is one or more of ethylenediamine, triethylamine, and diethylenetriamine; the solvent is ethanol or toluene; and the leveling agent is polyether-modified polydimethylsiloxane.

9. The method for preparing the insulating heat dissipating coating composition for lithium batteries according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: adding the modified epoxy resin to the solvent, mixing evenly, then adding the thermal conductive filler, stirring for 10-20 minutes, then adding the defoamer and the leveling agent, continuing to stir for 5-15 minutes, and finally adding the curing agent, stirring and mixing evenly, evenly coating the mixture on the mold surface, and curing and forming.

Citation Information

Patent Citations

  • Graphene heat dissipation paint, radiator coating and preparation method

    CN108003725A

  • Composite graphene three-prevention heat dissipation coat applied to electronic industry and preparation method thereof

    CN109929293A

  • Heat-resistant, thermal-insulation and anticorrosive coating composition and preparation method thereof

    CN113956751A

  • Steel wool-resistant light-cured polymer resin material and preparation method thereof

    CN118852542A

Cited By

  • Insulating weather-resistant powder coating and preparation method thereof

    CN119931500A

  • An insulating and weather-resistant powder coating and its preparation method

    CN119931500B

  • Outdoor waterproof convection heat insulation box for wireless communication equipment and heat conduction coating

    CN120603161A

  • Copper profile for chip radiator base and processing technology of copper profile

    CN120679954A